A Pilot Study Evaluation of 3-Dimensional Imaging in Cosmetic Breast Augmentation: Results of a Single Surgeon 3.5-Year Retrospective Study Using the BREAST-Q Questionnaire. Issue 1 (25th January 2021) - Hutchinson, Lauren E; Castaldo, Andrea D; Malone, Cedar H; Sommer, Nicole Z; Amalfi, Ashley N
Abstract: Background: Traditional methods of breast implant size selection provide limited ability to demonstrate postoperative outcomes. Three-dimensional (3D) imaging provides an opportunity for improved patient evaluation, surgical planning, and evaluation of postoperative breast appearance. Objectives: The authors hypothesized that preoperative 3D imaging for patients undergoing breast augmentation would improve patient satisfaction and understanding of expected surgical outcomes. Methods: A retrospective review of patients undergoing breast augmentation by a single surgeon over a 3.5-year period was performed. Patients presenting after the VECTRA was purchased had preoperative 3D imaging, while patients presenting before this did not. Eligible patients received a BREAST-Q questionnaire designed for postoperative evaluation of breast augmentation. They also received a second survey that evaluated expected vs actual breast outcomes. Results: In total, 120 surveys were mailed and 61 patients (50.8%) returned the survey. The 3D imaged group had improved BREAST-Q scores regarding satisfaction with outcome, surgeon, and physical well-being compared with the group that did not. The imaged group also had higher size, shape, and overall breast correlation scores, confidence in implant size selection scores, and communication with surgeon scores. The differences between the 2 groups were not statistically significant. Conclusions: Three-dimensional imaging is a valuable tool in breast surgery. Although this study showed improvement in patient satisfaction and predicted outcome scores in the 3D imaged group, the results were not statistically significant. With the majority of patients reporting that they would choose 3D imaging, it appears to instill confidence in patients regarding both surgeon and implant selection. Level of Evidence: 4: